Ambitions and obstacles for evidence-based municipal primary healthcare – a mixed- methods study - Monica Gustafsson; Magnus Zingmark; Susanne Iwarsson; Lisa Ekstam (Scandinavian Journal of Occupational Therapy)
Background Research is limited on registered healthcare professionals (RHCP) usage of research and evidence-based practice (EBP) in Swedish municipal primary healthcare work.Aim/Objectives The aim of this study was to increase the understanding of experiences, attitudes, and conditions of usage of research and implementation of EBP among RHCPs in a Swedish municipality setting. Further, the study aimed to explore whether those attitudes and conditions were associated with RHCP basing their work on research.Material and Methods The study was a mixed- methods study of a convergent design with five dialogue meetings and a web-based survey. Participants were RHCP recruited from one large size municipality.Findings Registered healthcare professionals struggled between personal and organisational conditions to use research and work according to EBP. They were torn between personal ambitions and lack of skills to use research, whereas having an advanced level education was significantly associated with basing work on research. Lack of organisational resources and support made usage of research and implementation of EBP difficult.Conclusion There is a need to strengthen the RHCP competence in using research evidence in clinical practice. Managemental support, education and clinical goals could improve the conditions for usage of research and implementation of EBP.